Note on the geographic distribution and morphology of Sisyrinchium platyphyllum (Iridaceae: Sisyrinchieae) - Martínez-Juárez, Daniela; Jiménez-Reyes, Noemí; Rodríguez, Aarón (Instituto de Ecología, A.C., 2013)
The presence of Sisyrinchium platyphyllum (Iridaceae) in six localities of the state of Jalisco, Mexico is documented. The species was first collected by Cyrus Guernsey Pringle on the southern rim of the Guadalajara canyon in 1889. Since then, its presence had not been documented again. Lastly, complete morphological and palynological descriptions and detailed figures are included.